Domestic capital formation, financial intermediation and economic development in Peru - Bernhard Fischer (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1987)
This paper focusses on the reasons of the poor performance of domestic resource mobilization in Peru. It begins with an analysis of the structure of domestic savings and its changes in the course of economic development (Section II) . After the description of the Peruvian financial sector (Section III) financial policies since the early 1970 are reviewed and the effects of financial repression discussed (Section IV). Finally some policy suggestions to improve domestic resource mobilization are presented.
Keywords: 330; Sparen; Bank; Entwicklung; Peru